MITOLOGI DAN SAINS: Bledug Kuwu di Kabupaten Grobogan - Aninditia Sabdaningsih (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
Bledug Kuwu is a unique mud volcano phenomenon located at Kuwu, Kradenan district, Grobogan Regency, Central Java. This area is far away from marine environment; however, this area contains high salinity hence none of plant and animal can live on this area. People believe about myth of arising mud volcano comes from the point where Joko Linglung, a giant snake, exit and enter the earth. Science has revealed about the origin of Bledug Kuwu and its potential. In this paper, Bledug Kuwu will be described from the local myth and multidisciplinary sciences.